Computational fluid dynamics study of flow behaviour in a single spacer filled membrane module - Hussain, Sharmina (BRAC University, 2010)
Membrane separation processes have added a new dimension to the traditional processes. The recent novel development in membrane processes have made it possible to use various different purposes at economical rates with additional flexibility and improved efficiencies. Regarding the membrane separation processes, concentration polarization is one of the biggest problems. It causes reduction of permeate flux and deterioration of permeate quality. Accumulation of rejected species can be suppressed by creating back mixing from the membrane to the bulk of the liquid. Various hydrodynamic approaches have been developed for that purpose. Feed spacers can provide higher shear rates at the membrane surface, which, promote the mixing between the bulk of the fluid and the fluid element adjacent to the membrane surface. As a result concentration polarization and membrane fouling can be reduced. The present work is devoted to investigate the hydrodynamics in two dimensional single spacer filled channels. Two different configurations of the cylindrical spacers are investigated with different channel Reynolds number. Different size and shape of formation of recirculation region, upstream and downstream of the spacers are closely observed. This recirculation region has an important role in enhancing the mass transfer in the reattachment region.